2020
DOI: 10.3844/ajavsp.2020.73.80
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Rate and Reproductive Disorders Examination of Inseminated Brahman Cross Cows by Rectal Palpation and Ultrasonography

Abstract: Pregnancy is a condition when a fetus began to develop in the uterus of the cow. Early pregnancy detection becomes important as it would determine the success of breeding management as well as to achieve the best productivity. This study aimed to evaluate and observe the pregnancy rate and reproductive disorders of Brahman Cross (BX) cows and compare the results to the Ultrasonography (USG) observation. The materials of the study were 80 BX cows selected through a purposive sampling method with the following c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The results obtained were similar to Ervandi et al (2020) that Brahman Crossbred cows fed low-quality feed will produce a low pregnancy rate. Haque et al (2015) also suggested that the variety of feed given to breeding cows (fresh forage, straw and concentrate mixture) increased reproductive hormone, resulting in a better pregnancy percentage.…”
Section: Pregnancy Ratesupporting
confidence: 84%
See 2 more Smart Citations
“…The results obtained were similar to Ervandi et al (2020) that Brahman Crossbred cows fed low-quality feed will produce a low pregnancy rate. Haque et al (2015) also suggested that the variety of feed given to breeding cows (fresh forage, straw and concentrate mixture) increased reproductive hormone, resulting in a better pregnancy percentage.…”
Section: Pregnancy Ratesupporting
confidence: 84%
“…Regarding the timing of artificial insemination, Ervandi et al (2020) also performed artificial insemination at almost the same hour (8-10 h after estrous detection); they showed that Brahman cows had a few numbers of pregnancy rate (27.5%, 11/40). In contrast, Sutiyono et al (2018) showed that the others breed cattle, Ongole Grade and Simmental-Ongole Crossbred, had a higher pregnancy rate (70.59 and 50.00%).…”
Section: Pregnancy Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, on T1, Pregnancy failure was in ten cattle, ovary hypofunction in five cattle (50,00%), and corpus luteum persistence in five cattle (50,00%). The result of the research, in line with Ervandi et al (2020), is that the decreased number of NRR in the Conception and Pregnancy Rate in cattle was caused by silent heat, premature embryo, ovary hypofunction, and corpus luteum persistence. Furthermore, the value of Services per Conception (S/C) did not significantly differ (P>0.05) between T0 and T1, while T1 had a lower S/C than T0.…”
Section: The First Conception Ratementioning
confidence: 72%
“…The NRR value was obtained by observing lust on days 19-21 and days 40-42 after AI. If there are no signs of lust, it is assumed that she is pregnant and if there are signs of lust, it is assumed that she is not pregnant, a repeat AI will be carried out [7,8].…”
Section: Variablesmentioning
confidence: 99%